2017
DOI: 10.1016/j.pmedr.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care testing to promote cardiovascular disease risk assessment: A proof of concept study

Abstract: Updated cholesterol guidelines emphasize multivariable cardiovascular disease (CVD) risk estimation to guide treatment decision-making in primary prevention. This study tested the preliminary feasibility, acceptability and efficacy of point-of-care testing (POCT) and quantitative CVD risk assessment in high-risk adults to increase guideline-recommended statin use in primary prevention. Participants were aged 40–75 years, without CVD or diabetes mellitus, and potentially-eligible for consideration of statins ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…As a result, participants expressed a high level of satisfaction with the intervention. (27). A separate study aimed at assessing patient satisfaction with POCT in a general practice setting indicated that patients exhibited higher levels of satisfaction and con dence with this testing method.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, participants expressed a high level of satisfaction with the intervention. (27). A separate study aimed at assessing patient satisfaction with POCT in a general practice setting indicated that patients exhibited higher levels of satisfaction and con dence with this testing method.…”
Section: Discussionmentioning
confidence: 98%
“…Besides all the medical information for each of the patients this database in full can be used for public health policies [13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The 2013 ACC/AHA PCEs have been widely referenced in guidelines as detailed in the previous section, 21,24,28 validated extensively in external datasets, [31][32][33][34] and implemented broadly in clinical care. [35][36][37][38] With changing prevalence of risk factors (eg, tobacco use), secular trends in risk factor levels (eg, declines in lipid levels in the past decade 39,40 ), changes in care patterns (eg, more widespread use of various antihypertensive therapies), risk for incident ASCVD can be overestimated with the PCEs. 41 As a result, the CKM Health SAG agreed that it was now time to revise and update risk equations to address several key gaps in risk prediction with the PCEs and other existing models.…”
Section: Rationale For the Development Of Novel Risk Prediction Equat...mentioning
confidence: 99%